EVALUASI PERTUMBUHAN DAN KEPADATAN STOMATA TANAMAN SORGUM YANG DIBUDIDAYAKAN DI LINGKUNGAN BASAH DENGAN BERBAGAI POLA PENGAIRAN - Edi Susilo; Dian Novita; Tatik Raisawati; Andreani Kinata; Hesti Pujiwati (BPFP Universitas Bengkulu, 2024)
[ASSESING GROWTH AND STOMATAL DENSITY OF CULTIVATED SORGHUM PLANTS IN WETLAND ENVIRONMENTS ACROSS DIFFERENT IRRIGATION PATTERNS]. Sorghum cultivation is commonly associated with dry lands, but its potential for development on marginal swamp land remains limited. The wet conditions characteristic of swamp land pose a unique challenge to sorghum cultivation in Indonesia. This study sought to gather preliminary insights into sorghum crop development on swamp land by examining the effects of different irrigation patterns. Conducted at the Bengkulu University Greenhouse from June to August 2022, the research employed a group-randomized design with a single-factor pattern. Four irrigation treatments were administered: saturated water, saturated dry, dry-saturated, and dry. The experimental unit consisted of polybag planting media, repeated four times, with each polybag containing 20 seeds of the Numbu sorghum variety, cultivated until reaching six weeks of age. Irrigation patterns were simulated by placing the polybag media in basins filled with water up to a height of 10 cm. Results revealed varying impacts of irrigation patterns on sorghum growth, with water-saturated, dry-saturated, and dry-saturated patterns leading to superior growth compared to the dry pattern. Notably, sorghum plants cultivated under wet conditions on swamp land exhibited promising growth